Efluvio telógeno y Covid-19 - Verástegui G., Andrea; Zemelman D., Viviana; Guerrero C., Silvia (Revista Hospital Clínico Universidad de Chile, 2022)
Introduction: The first case of infection by the virus SARS-CoV-2 was reported in China in the late 2019. The disease caused by this virus was called COVID-19 and was declared as a global pandemic by World Health Organization in March 2020. Among the consequences caused by the virus, some dermatological pathologies have been reported, such as Telogen effluvium (TE). In this review we will address the relation between Telogen effluvium and COVID-19. Material and methods: All literature related to Telogen effluvium and COVID-19 was searched in PubMed. Results: Since the beginning of the pandemic, the number of patients diagnosed with TE has increased. This is explained on one hand by the infection itself of the virus, generating a proinflammatory and procoagulant answer that lead to TE. On the other hand, it can be explained due to the stress caused by the lockdowns and the psychological consequences of a global pandemic. Also, the therapies used to treat the infection may increase the severity of the TE. The relation between TE and Covid-19 is not totally clear yet, but it is important due to the great impact that generates in the lives of the patients.